2015
DOI: 10.1210/jc.2014-4328
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hair Cortisol Concentrations and BMI in Patients With Pituitary-Adrenal Disease on Hydrocortisone Replacement

Abstract: Physiological hydrocortisone replacement is associated with increased CORT(hair). The association between CORT(hair) and BMI could suggest a mild overtreatment that may lead to adverse anthropomorphic side effects, especially in males. CORT(hair) measurements may be a promising additional tool to monitor cumulative hydrocortisone replacement in AI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
3
22
1
Order By: Relevance
“…However, null associations between socioeconomic status and hair cortisol have also been reported (Bosma et al . 2015; Staufenbiel et al . 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, null associations between socioeconomic status and hair cortisol have also been reported (Bosma et al . 2015; Staufenbiel et al . 2015).…”
Section: Introductionmentioning
confidence: 99%
“…2014; Rippe et al . 2016; Staufenbiel et al . 2015 for other large-scale studies of hair cortisol in singletons).…”
Section: Introductionmentioning
confidence: 99%
“…All studies reported higher mean HCC in hydrocortisone-treated patients compared to healthy individuals or non-AI controls. In the two studies performed in adult AI patients, (19,20), while in the other two studies, HCC correlated significantly with BMI but not with hydrocortisone dose (21,22). In the adrenocortical carcinoma patients, this can be explained by mitotane treatment, which alters the metabolism of hydrocortisone.…”
Section: Hydrocortisone Replacement Therapy Monitoringmentioning
confidence: 89%
“…Several published studies have investigated HCC in patients treated with hydrocortisone for AI. The studies included 132 adults with AI, 93 adults with AI, 54 children with AI and 15 adults who were treated with the adrenolytic drug mitotane for adrenocortical carcinoma (19,20,21,22). All studies reported higher mean HCC in hydrocortisone-treated patients compared to healthy individuals or non-AI controls.…”
Section: Hydrocortisone Replacement Therapy Monitoringmentioning
confidence: 99%
“…The measurement of HCC may constitute an important, long term biomarker of stress [14]. Newer studies have established age and gender [15], season, hair characteristics, sociodemographic factors, health and body mass index [16, 17] as determinants of HCC to be included when studying HCC.…”
Section: Introductionmentioning
confidence: 99%